Micro Pitting And Wear Assessment Of Spur Gear - Abd Ghani, Muhammad Muzakkir (Universiti Sains Malaysia, 2022)
Micro pitting and wear are one of the most common phenomena in gear parts where it becomes the thing that causes machine damage. The damage to this machine will have a very big impact because it requires an engineer to repair the damaged machine parts and it consumes a relatively high cost even though the damage faced by the gear parts is only small - scale. Proper lubrication is crucial to avoid gear failure. It is necessary to identify the influence of lubricants on the dispersion and wear of micro pitting, as well as to identify any significant influences that may occur when additives are applied to samples. The main purpose of this study was to study the micro pitting and wear behaviours of palm oil base grease in spur gear and to evaluate the performance of biodegradable grease compared with and without nanoparticle MoS2 as an additive. In this study, the experiment is carried out using a gear test rig and the test is run under three different conditions. Surface scanning was done to evaluate the gear surface profiles. The finding shows that the gear lubricated with palm oil grease with MoS2 additive has less micropitting depth and wear. This indicates that the additive manages to reduce the surface damage efficiently and is compatible with the palm grease.